FAKTOR FAKTOR YANG MEMPENGARUHI PENERIMAAN UNQUALIFIED OPINION WITH MODIFIED PARAGRAPH GOING CONCERN PADA SEKTOR NON KEUANGAN YANG TERDAPAT DI BURSA EFEK INDONESIA - Glenn Martinus Marjono (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2013)
The purpose of this study is to investigate factors that influence unqualified opinion with modified paragraph going concern. Factors which this study research are debr default, auditor’s quality, opinion shopping, financialdistress, prior opinion, and growth. The study process the data from independent auditor’s report of the go public companies in Indonesia over four years period 2008 – 2011. The data used in this study are chosen by purposive sampling method with four criterias. The study explores debt default, opinion shopping and prio opinion with dummy approach and formula for financial distress dan growth. Logistic regression is used for this study and selection of likelihood ratio to value properness of model. This research’s summary is given. Debt default has statistically significant to influence unqualified opinion with modified paragraph going concern. Auditor’s quality and opinion shopping haven’t statistically significant to influence unqualified opinion with modified paragraph going concern. Prior opinion has statistically significant to influence unqualified opinion with modified paragraph going concern. Depend on financial distress and growth’s formula can be conclude, they haven’t statistically significant to influence unqualified opinion with modified paragraph going concern.